2014
DOI: 10.1080/1034912x.2014.934004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Comprehension Skill on Inference Generation during Reading

Abstract: The purpose of this study was to investigate differences between readers with different levels of comprehension skill when engaging in a causal questioning activity during reading, and the varied effects on inference generation. Fourth-grade readers (n = 74) with different levels of comprehension skill read narrative texts aloud and were asked causal questions at specific points during reading. Responses to questions were examined for the types of inferences the readers made during reading. There was no main e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…However, given the overlaps between listening and reading comprehension tasks, research from the latter modality provides useful background information for this study. Carlson et al (2014) found no overall difference in the number of inferences generated by 9-10 year olds with different levels of comprehension skill when asked causal questions during reading. This contrasts with findings from studies that use the traditional approach, assessing comprehension after reading is completed (Oakhill, 1984, e.g.…”
Section: Assessing Children's Inference Making: the Effect Of Text Fomentioning
confidence: 64%
See 2 more Smart Citations
“…However, given the overlaps between listening and reading comprehension tasks, research from the latter modality provides useful background information for this study. Carlson et al (2014) found no overall difference in the number of inferences generated by 9-10 year olds with different levels of comprehension skill when asked causal questions during reading. This contrasts with findings from studies that use the traditional approach, assessing comprehension after reading is completed (Oakhill, 1984, e.g.…”
Section: Assessing Children's Inference Making: the Effect Of Text Fomentioning
confidence: 64%
“…Thus, better comprehension ability for passages presented in a segmented format gives an indication about whether any difficulties arise from a tendency to process text in a piecemeal fashion rather than integrating information into the mental model as the text unfolds to ensure high standards of coherence. It may be the case that individuals currently identified as having comprehension difficulties are capable of making sufficient inferences to maintain coherence as they process text , but that existing measures are not sufficiently sensitive to capture this because comprehension questions are traditionally asked at the end of the task (Carlson et al, 2014). Therefore the segmented format should allow comparisons between inferences that are generated during the story and those that are identified after the material has been presented.…”
Section: Assessing Children's Inference Making: the Effect Of Text Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Para lograr esta representación, el lector debe conectar ideas provenientes de diferentes partes del texto e integrarlas (Abusamra, & Joanette, 2012), esto es, debe realizar inferencias y conexiones entre la información literal explícita (Elbro & Buch-Iversen, 2013;van den Broek & Kendeou, 2008). La generación de inferencias se refiere a la activación de información que no se encuentra explícitamente enunciada durante la lectura para dar mayor coherencia a la oración focal que se está leyendo (Carlson et al, 2014;Freed & Cain, 2016;van den Broek, Risden, Fletcher, & Thurlow, 1996).…”
Section: Introductionunclassified
“…Researchers have reached some consistency regarding instructional practices that succeed in improving reading ability of adolescent struggling learners (Berkeley et al, 2010;Kamil, Borman, Dole, Kral, Salinger, & Torgesen, 2008;Swanson & Deshler, 2003). These practices include strategies for reading multisyllabic words and understanding what they mean, and also for integrating words, phrases, and passages to construct mental representations of what they read (Carlson et al, 2014;Kintsch, 1988). Instruction in preparatory skills students may need, such as letter patterns, affixes, and morphemes (i.e., meaningful parts of words), need to be integrated with opportunities to apply these skills to words that are appropriate for students' age and grade (Ebbers & Denton, 2008).…”
mentioning
confidence: 99%